2021
DOI: 10.1080/07853890.2021.1927169
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori increases the risk of carotid plaque formation: a clinical evidence

Abstract: Background and aim: Since the relation between Helicobacter pylori ( H. pylori ) and atherosclerosis has been evidenced, we aimed to analyze whether there is a relationship between the patient's H. pylori infection and age, gender, BMI, blood lipids, and carotid plaque formation. Methods: 810 patients from January 2016 to December 2019 were enrolled in this study, and divided the subjects into H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…H. pylori infection activates multiple signal transduction pathways that promote inappropriate inflammatory responses and contributes to pathological changes in lipid metabolism and epithelial cell proliferation, survival, and function [ 30 ]. Those events associated with H. pylori are closely related to plaque formation and stability [ 31 , 32 ]. Overall, functional analysis by GO and KEGG annotation revealed the important roles of upregulated circRNAs in regulating the plaque stability of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection activates multiple signal transduction pathways that promote inappropriate inflammatory responses and contributes to pathological changes in lipid metabolism and epithelial cell proliferation, survival, and function [ 30 ]. Those events associated with H. pylori are closely related to plaque formation and stability [ 31 , 32 ]. Overall, functional analysis by GO and KEGG annotation revealed the important roles of upregulated circRNAs in regulating the plaque stability of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the association between compositional differences in the gut flora and AS [ 114 – 116 ]. In addition, the nucleic acid components of some parenteral pathogenic bacteria have been successively identified in atherosclerotic plaques, such as Porphyromonas gingivalis, Helicobacter pylori, and Chlamydia pneumoniae, which are also important for the progression of AS [ 117 119 ]. Therefore, imbalances in gut microbial homeostasis or infection with pathogenic microbes may serve as novel risk factors for AS.…”
Section: Effects Of Probiotics On Novel As Progression Factorsmentioning
confidence: 99%
“…A growing number of observational studies have linked AS to H. pylori. 16,17 Previous studies have suggested that the link may be caused by a chronically infected environment in the body, 18 but there are opposing views that may be there are common risks such as aging, unhealthy diet, and smoking between these. 19 Metaanalysis is an effective way to resolve clinical disputes.…”
Section: Introductionmentioning
confidence: 99%